The effectiveness of computerized training of visual-motor skills on visual- motor skills children with Attention Deficit-Hyperactivity Disorder - Ali Kermani (روانشناسی و روانپزشکی شناخت, 2021)
Introduction: Attention Deficit-Hyperactivity Disorder (ADHD) is one of the most common childhood disorders. An important subset of these children faces motor problems, including motor skills and motor coordination. Aim: The present study was performed in order to investigate the effectiveness of computerized training of visual- motor skills on visual- motor skills of children with Attention Deficit-Hyperactivity Disorder. Method: The present study was experimental research with a pretest- posttest design and with a control group. The statistical population of the study included all male students with Attention Deficit-Hyperactivity Disorder who were studying in the elementary school of Mashhad during the academic year 2019-2020. 30 students were randomly replaced (15 students in experimental group and 15 students in control group) by Connor's Teacher Rating Scales (CTRS). Instruments included a researcher computer game made by Rayapouya based on Cog Pack software, Conner's Teacher Rating Scale (1969), and Test of Visual-Motor Skills - third edition (TVMS-3). Data were analyzed by univariate analysis of covariance in the SPSS-23 software environment. Results: The research findings indicated that computerized training of visual- motor skills has been effective in improving visual-motor skills (P<0.01) of children with Attention Deficit-Hyperactivity Disorder and 35.4% of the differences in post-test scores of visual- motor skills are related to computerized training of visual- motor skills (P<0.01). Conclusion: According to the research findings, it seems that computerized training of visual-motor skills is an effective treatment that improves the performance of visual- motor skills.